2022
DOI: 10.3390/foods11020188
|View full text |Cite
|
Sign up to set email alerts
|

Omics Approaches to Assess Flavor Development in Cheese

Abstract: Cheese is characterized by a rich and complex microbiota that plays a vital role during both production and ripening, contributing significantly to the safety, quality, and sensory characteristics of the final product. In this context, it is vital to explore the microbiota composition and understand its dynamics and evolution during cheese manufacturing and ripening. Application of high-throughput DNA sequencing technologies have facilitated the more accurate identification of the cheese microbiome, detailed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 256 publications
(341 reference statements)
1
12
0
Order By: Relevance
“…In the ripening process, a general increase in flavor is associated with the production of a wide range of volatile compounds during ripening through the metabolism of triglycerides and proteins [ 22 ]. The pasteurization of cows’ milk reduced aromatic intensity and lactic flora, but the addition of donkey milk and freeze-dried Streptococcus thermophilus lactic ferments improved the microbiome of Caciotta made from mixed milk and the diversification of flavors in short-ripened cheeses, as also shown in other recent studies [ 1 , 7 ]. In these studies, the addition of L .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the ripening process, a general increase in flavor is associated with the production of a wide range of volatile compounds during ripening through the metabolism of triglycerides and proteins [ 22 ]. The pasteurization of cows’ milk reduced aromatic intensity and lactic flora, but the addition of donkey milk and freeze-dried Streptococcus thermophilus lactic ferments improved the microbiome of Caciotta made from mixed milk and the diversification of flavors in short-ripened cheeses, as also shown in other recent studies [ 1 , 7 ]. In these studies, the addition of L .…”
Section: Discussionsupporting
confidence: 66%
“…At this stage, the sensory quality of Caciotta can be altered by aromas resulting from undesirable fermentation and by excessive concentrations of bitter oligopeptides [ 6 ]. The microbiota of cheese come from three sources: the native milk microbiota, the inoculated enzymes, and the cheesemaking environment [ 7 ]. A fundamental aspect affecting the microbiota is hygiene throughout the supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…22 In particular, metabolomics is a new field that allows identification and quantification of low molecular mass (e.g., organic acids, carbohydrates, amino acids, peptides, nucleic acids, vitamins, and minerals), and it is specific or nonselective. 23 For proteomic analysis, several analytical techniques are necessary for the correct separation, detection, identification, and quantification of bioactive compounds contained in the cheese matrix. 24 In this sense, some analytical techniques used for separation are liquid chromatography (LC), of which we can mention high-performance (HPLC) or ultrahigh performance (UHPLC), gas chromatography, and capillary electrophoresis, coupled to mass spectrometry, and also highsensitivity and high-resolution (HR) tandem mass spectrometry (MS).…”
Section: Of Bioactive Compoundsmentioning
confidence: 99%
“…For proteomic analysis, several analytical techniques are necessary for the correct separation, detection, identification, and quantification of bioactive compounds contained in the cheese matrix . In this sense, some analytical techniques used for separation are liquid chromatography (LC), of which we can mention high-performance (HPLC) or ultrahigh performance (UHPLC), gas chromatography, and capillary electrophoresis, coupled to mass spectrometry, and also high-sensitivity and high-resolution (HR) tandem mass spectrometry (MS) . Analysis of proteins is a complex task due to the experimental different changes (e.g., charge, size, hydrophobicity, phosphorylation, acetylation, or glycosylation) during cheese making.…”
Section: Analytical Techniques For Identification Of Bioactive Compoundsmentioning
confidence: 99%
“…[ 77 ]. A review of the Arthrobacter strain and its ability to produce numerous enzymes have revealed the potential of this genus for the synthesis of MGL [ 78 , 79 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%